The value of coronary computed tomography angiography in assessing the cardiac circulation of an outpatient-based population - Chen, Xiaoxia; Wang, Guisheng; Zhao, Lin; Zhao, Jingwei; Liu, Ting; Zhao, Guoquan; Han, Wenjuan (Medicine (Baltimore), 2020)
To evaluate the perfusion of coronary circulation and its related factors and the difference in the peak filling times in aortic sinus and coronary sinus by coronary computed tomography angiography (CCTA).From January 1 to August 1, 2018, 61 outpatients with angina pectoris were recruited, completed a questionnaire about risk factors and underwent CCTA, which was also used to assess the stenosis of different coronary artery segments.The duration of circulation was 9.50 ± 2.43 seconds in patients with flat T wave, which was shorter than the duration in normal subjects (P = .021). However, other cardiovascular risk factors showed no effect on the duration of circulation. In addition, the duration of circulation was closely related to the peak filling time of coronary sinus [r(s) = 0.681]. We further divided the circulation time difference (delta) values into 3 levels (<6, 6-12, and ≥12 seconds).It showed that the circulation duration (Y) was associated with:Therefore, the cardiac circulation duration was negatively related to the degree of stenosis in the 1 diagonal and proximal LCA.It compensates for the inability of CCTA to assess circulation at rest simply by determining the peak filling time in the aortic sinus and the coronary sinus. Moderate cardiac microcirculation duration was related to a low incidence of clinical symptoms and electrocardiogram disorders, which was determined mainly by the diagonal and left circumflex branch 1 of LCA.